Ainda sobre os cerieiros de Penafiel e o fabrico de cera em Ribas (Lagares) - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Complement to the article, which was published in this magazine last issue, on the beeswax chandler occupation and installation of beeswax presses in Penafiel district. This additional information shows new data about the owners of the production center in Ribas (Lagares). Genealogical appendix of the holding family (by Eduardo Vasconcelos).